Homo Futurus : 15 Flash artists present their idea of man of the future. Made of about 600.000 LEGO elements, etc. (Odense : Kunsthallen Brandts Klaedefabrik, 1989)
Balsgaard, Jane ; Bonanno, Alfio ; Diedrichsen, Ulla ; Fomer Hansen, Ole ; Holdensen, Annette ; Hvid, Hans Jorgen ; Inoue, Junichi ; Jensen, Jan ; Kramer, Per ; Krull Oldau, Hans ; Lykkegaard, Eva ; Madsen-Ambeck, Peter ; Harvey, Martin ; Mikkelsen, Leif ; Pedersen, Felix ; Jorn, Ronnau ; Seisboll, Lise ; Troelsen, Frede
Homo Futurus : 15 Flash artists present their idea of man of the future. Made of about 600.000 LEGO elements, etc., Kunsthallen Brandts Klaedefabrik, Odense, March 11 to May 7, 1989
boek